1999
DOI: 10.1001/archotol.125.11.1214
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility of the Cochlear Implant in Adults<subtitle>A Meta-analysis</subtitle>

Abstract: Profound deafness in adults results in a substantial health-utility loss. Over half of that loss is restored after cochlear implantation, yielding a cost-utility ratio of $12,787 per QALY. This figure compares favorably with medical and surgical interventions that are commonly covered by third-party payers in the United States today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 19 publications
3
73
2
3
Order By: Relevance
“…costs on medical reimbursement levels, which have been argued to underestimate the true hospital costs of implantation (Cheng & Niparko, 1999;Cheng et al, 2000;Garber, et al, 2002;Summerfield et al, 2003). Additionally, Barton et al (2006a) demonstrated that our estimates of the educational costsavings associated with implantation may be smaller than those reported by Cheng et al (2000) and O'Neill et al (2000) because we controlled for more confounding variables.…”
Section: Ear and Hearing / October 2006mentioning
confidence: 63%
See 2 more Smart Citations
“…costs on medical reimbursement levels, which have been argued to underestimate the true hospital costs of implantation (Cheng & Niparko, 1999;Cheng et al, 2000;Garber, et al, 2002;Summerfield et al, 2003). Additionally, Barton et al (2006a) demonstrated that our estimates of the educational costsavings associated with implantation may be smaller than those reported by Cheng et al (2000) and O'Neill et al (2000) because we controlled for more confounding variables.…”
Section: Ear and Hearing / October 2006mentioning
confidence: 63%
“…Third, the health-service costs of implantation were based on reimbursement levels rather than actual costs. Reimbursement levels do not always provide a good estimate of the true cost of the resources consumed in providing heath care (Beck, Beecham, Mandalia, Griffith, Walters, Boulton, & Miller, 1999), and there is evidence that the level of public reimbursement for cochlear implantation in the United States is often below cost (Cheng & Niparko, 1999;Garber, Ridgely, Bradley & Chin, 2002).…”
Section: Ear and Hearing / October 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,15 However, cochlear implantation is a low volume, high cost medical intervention. In spite of tremendous improvements in the technology of cochlear implantation, the cost of the device has remained high (between $15 000 and $35 000, depending upon the manufacturers and local market).…”
Section: Discussionmentioning
confidence: 99%
“…32 Nevertheless, we are currently aware of several examples of reviews or systematic reviews conducted in the health care field in which the authors have pooled either resource use or cost estimates [33][34][35][36][37][38] or cost-utility ratios. 39 The review by Bower and colleagues 34 is summarised as a case study in Box 3.3.…”
Section: Guidance For Conducting Systematic Reviews Of Economic Studiesmentioning
confidence: 99%